2003
DOI: 10.1163/156853903322149469
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual Signalling By the Lizard Anolis Carolinensis, with Intersexual Comparisons Across Contexts

Abstract: SummaryWe quanti ed the structure and use of signals exchanged by males and females within the female-defence polygyny of the lizard, Anolis carolinensis. During heterosexual interactions, both sexes performed three kinds of stereotypic headbob displays (A, B, and C) with equal precision. These three display types were essentially identical to A, B, and C display types previously documented for both sexes during consexual contests, and for males when displaying alone (non-directed context). Therefore, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 90 publications
1
55
1
Order By: Relevance
“…Such signals allow a rival male or female to identify the quality of a dominant individual without having to engage in physical combat (Osborne 2005). Specific display behaviors may transmit information about an individual's aggressiveness to conspecifics and thereby influence the outcome of dominance interactions (Hover and Jenssen 1976;Orrell and Jenssen 2003;Osborne 2005). Our results showed that resident males of P. vlangalii engaged in tail curling and agonistic interactions more frequently than floater males.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Such signals allow a rival male or female to identify the quality of a dominant individual without having to engage in physical combat (Osborne 2005). Specific display behaviors may transmit information about an individual's aggressiveness to conspecifics and thereby influence the outcome of dominance interactions (Hover and Jenssen 1976;Orrell and Jenssen 2003;Osborne 2005). Our results showed that resident males of P. vlangalii engaged in tail curling and agonistic interactions more frequently than floater males.…”
Section: Discussionmentioning
confidence: 68%
“…Displays are important visual signals (Kim 1995;Zug et al 2001;Brandt 2003), and are known to predict a lizard's aggression, endurance and performance capacity (Hover and Jenssen 1976;Brandt 2003;Orrell and Jenssen 2003;Perry et al 2004;Osborne 2005). Such signals allow a rival male or female to identify the quality of a dominant individual without having to engage in physical combat (Osborne 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were then able to choose the proper recording method based on the characters of different behavioral elements. For example, time sampling is suggested to be suitable for the recording of acts, whereas instantaneous sampling may be more suitable for the recording of postures (Orrell and Jenssen, 2003;Bloch and Irschick, 2006;Martin and Bateson, 2007).…”
Section: Function Of Ethogram Establishment Of An Ethogrammentioning
confidence: 99%
“…Stereotypical behaviors, dewlap and/ or nuchal crest extension, lateral compression, body color and eyespots are the most obvious signals, and are used for different functions, and produce different neurochemical output in male and female Anolis carolinensis [1,19,69,79]. Highly ritualized behavioral displays are characterized by three display action patterns of head nods and dewlap extension, with tempo but not cadence distinguishing function [58]; the imparted messages depending on context plus the rank and sex of the lizard [1,19,70,79]. It may be that different components from a multilayered signal redundancy, which includes the eyespots, are important for opponent recognition in A. carolinensis, as has been demonstrated for mate recognition in frogs [63].…”
Section: Agonistic Behavior and Social Status Response To A Second Somentioning
confidence: 99%